Virtual Reality-Based Executive Function Rehabilitation System for Children With Traumatic Brain Injury: Design and Usability Study - Shen, Jiabin; Xiang, Henry; Luna, John; Grishchenko, Alice; Patterson, Jeremy; Strouse, Robert V; Roland, Maxwell; Lundine, Jennifer P; Koterba, Christine H; Lever, Kimberly; Groner, Jonathan I; Huang, Yungui; et al. (JMIR Publications, 2020)
BackgroundTraumatic brain injury (TBI) poses a significant threat to children's health. Cognitive rehabilitation for pediatric TBI has the potential to improve the quality of life following the injury. Virtual reality (VR) can provide enriched cognitive training in a life-like but safe environment. However, existing VR applications for pediatric TBIs have primarily focused on physical rehabilitation. ObjectiveThis study aims to design and develop an integrative hardware and software VR system to provide rehabilitation of executive functions (EF) for children with TBI, particularly in 3 core EF: inhibitory control, working memory, and cognitive flexibility. MethodsThe VR training system was developed by an interdisciplinary team with expertise in best practices of VR design, developmental psychology, and pediatric TBI rehabilitation. Pilot usability testing of this novel system was conducted among 10 healthy children and 4 children with TBIs. ResultsOur VR-based interactive cognitive training system was developed to provide assistive training on core EF following pediatric TBI. Pilot usability testing showed adequate user satisfaction ratings for both the hardware and software components of the VR system. ConclusionsThis project designed and tested a novel VR-based system for executive function rehabilitation that is specifically adapted to children following TBI.